Hydrogen sulfide attenuates disturbed flow-induced vascular remodeling by inhibiting LDHB-mediated autophagic flux - Xia Wang; Xiying Huang; Yongya Zhang; Huanhuan Huo; Guo Zhou; Linghong Shen; Long Li; Ben He (Redox Biology)
Disturbed flow (DF) plays a critical role in the development and progression of cardiovascular disease (CVD). Hydrogen sulfide (H2S) is involved in physiological processes within the cardiovascular system. However, its specific contribution to DF-induced vascular remodeling remains unclear. Here, we showed that the H2S donor, NaHS suppressed DF-induced vascular remodeling in mice. Further experiments demonstrated that NaHS inhibited the proliferation and migration of vascular smooth muscle cells (VSMCs) induced by platelet-derived growth factor-BB (PDGF), as well as the autophagy triggered by DF and PDGF. Mechanistically, RNA-Seq results revealed that NaHS counteracted the PDGF-induced upregulation of lactate dehydrogenase B (LDHB). Overexpression of LDHB abolished the protective effect of NaHS on DF-induced vascular remodeling. Furthermore, LDHB interacted with vacuolar-type proton ATPase catalytic subunit A (ATP6V1A), leading to lysosomal acidification, a process that was attenuated by NaHS treatment. The residues of leucine (Leu) 57 in ATP6V1A and serine (Ser) 269 in LDHB are critical for their interaction. Notably, the expression of LDHB was found to be elevated in vascular tissues from patients with abdominal aortic aneurysms (AAA) and thoracic aortic aneurysms (TAA). These data identify a molecular mechanism by which H2S attenuates DF-induced vascular remodeling by inhibiting LDHB and disrupting the interaction between LDHB and ATP6V1A, thereby impeding the autophagy process. Our findings provide insight that H2S or targeting LDHB has therapeutic potential for preventing and treating vascular remodeling.